Pengaruh Korean Brand Ambassador Credibility, Social Media Marketing, dan Fear of Missing Out Terhadap Impulse Buying pada Kolaborasi Scarlett Whitening X EXO - Dita Keysia Armelia Dwi Putri; Jojok Dwiridotjahno (Reslaj: Religion Education Social Laa Roiba Journal, 2024)
The study aims to find out and analyze the impact of Korean brand ambassador credibility, social media marketing, and fear of missing out (fomo) on impulse buying for the collaboration product Scarlett Whitening X EXO, both simultaneously and partially. This research uses a quantitative approach with the type of associative research. As for data collection using questionnaires with populations involving EXO fans who are active on social media and have purchased collaboration products like Scarlett Whitening X EXO, The sampling technique used is the Lemeshow formula, and samples of research were obtained from as many as 100 respondents. The data processing method in this study uses the SPSS 26 application. Instrument testing uses validity tests and reliability tests, with results showing that the entire instrument is declared valid and reliable. Data analysis techniques use double linear regression, classical assumption tests, f tests, t tests, and determination tests. The results of this study based on trial analysis showed that Korean brand ambassador credibility, social media marketing, and fear of missing out (fomo) partially had a significant influence on impulse buying, while simultaneously Korean brand ambassador credibility, social media marketing, and fear of missing out (fomo) had significant influences on impulsive buying. The determination coefficient is 0.590. That is, 59% indicated that impulse buying was influenced by Korean brand ambassador credibility, social media marketing, and fear of missing out (fomo) variables, while the remaining 41% were affected by other variables that have not been studied.